Studies On Determination Of Susceptibility To Dental Caries Among School Children - S.N. DESHPANDE; D.G. KADAM; SACHIN B INGLE (International Journal of Pharma and Bio Sciences, 2012)
Dental caries is a multifactorial disease. The interactions of various factors like microorganisms, carbohydrate diet, hygiene habits and socioeconomic status are involved in causation of dental caries. For assessment of dental caries few tests demonstrating oral bacteria and their products have been accepted as these oral microflora and their products play an important role in causation and progression of dental caries. In the present study, susceptibility to dental caries was determined by Snyder test and Lactobacillus count. To study the risk factors associated with dental caries, a self designed questionnaire was distributed among the school children. About 84% children were found to be susceptible to dental caries.The Snyder test is more simple and rapid to perform as compared to Lactobacillus count in carrying out large surveys for assessment of dental caries. The study of other risk factors is also equally important in determination of risk of dental caries.